PEMBUATAN ZAT WARNA ALAMI DARI BIJI KESUMBA DALAM BENTUK KONSENTRAT TINGGI UNTUK PEWARNA MAKANAN - Paryanto, Paryanto; Hermiyanto, Hermiyanto; Sanjaya, Simon Dicky Surya (METANA, 2013)
Abstract The use of synthetic dyes for food in Indonesia reached 88%, this figure is quite alarming considering the health effects of synthetic dyes. So that needs to be made of natural dyes to replace the synthetic dyes. Like the natural pigments bixin of the annatto seed can give a yellow color to red. This study was conducted to determine how to produce natural pigments bixin from annatto seed using extraction process and how the optimum conditions and their application in food.Factors affecting the extraction process among other types of solvents, the size of the material to be extracted, temperature and extraction time, the ratio of material to solvent and stirring speed. Bixin will be degraded when heated and will turn into norbixin when there is excess salt sodium (Na) or potassium (K). Bixin extraction from the seeds annatto using a solvent acetone (CH3COCH3) and sodium hydroxide (NaOH) with variations in concentration, extraction temperature, stirring speed and the ratio of material to solvent. For bixin analysis using UV-Vis spectrophotometer, bixin will produce a maximum absorbance at a wavelength of 470 nm and using FTIR spectrophotometer to determine the group of bixin.The water content in the seeds kesumba is 37% and has a total of 10% bixin content. The optimum conditions of the extraction process of seed kesumba bixin is the type of solventNaOH with a concentration of 0.25 N, extraction temperature of 60 oC, 400 rpm stirring speed and weight of material to solvent ratio 1:20 by weight 2192 mg extract. Keywords: Extraction, bixin, annatto, bixa orellana, sodium hydroxide